ПРЕДГОВОР (Journal of Contemporary Philology, 2022)
This special issue of the Journal of Contemporary Philology contains selected articles presented at the ESIDRP 2022 conference, English Studies at the Interface of Disciplines: Research and Practice, organised by the Department of English Language and Literature, Ss. Cyril and Methodius University in Skopje. Around one hundred academics participated in the conference, whose main aim was to foreground the value of exploring issues in the discipline of English Studies from a variety of interdisciplinary perspectives.